2007
DOI: 10.1002/art.22834
|View full text |Cite
|
Sign up to set email alerts
|

HLA–DRB4 as a genetic risk factor for Churg‐Strauss syndrome

Abstract: Objective. To explore the association between HLA alleles and Churg-Strauss syndrome (CSS), and to investigate the potential influence of HLA alleles on the clinical spectrum of the disease.Methods. Low-resolution genotyping of HLA-A, HLA-B, and HLA-DR loci and genotyping of TNFA ؊238A/G and TNFA ؊308A/G single-nucleotide polymorphisms were performed in 48 consecutive CSS patients and 350 healthy controls.Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 43 publications
2
83
0
5
Order By: Relevance
“…HLA-DRB4 positivity may be a genetic risk factor for the development of CSS and may increase the likelihood of vasculitic manifestations of the disease. 5 Although this patient met only three of the six proposed ACR criteria, the clinical signs of her condition were most distinctive and in keeping with a diagnosis of CSS on clinical grounds. Indeed, Lanham et al have reported that although the classical histological picture comprises a necrotizing vasculitis, eosinophilic tissue infiltration and extravascular granulomas, it is only found in a minority of cases, and is not pathognomonic of the condition.…”
Section: To the Editorsupporting
confidence: 53%
See 1 more Smart Citation
“…HLA-DRB4 positivity may be a genetic risk factor for the development of CSS and may increase the likelihood of vasculitic manifestations of the disease. 5 Although this patient met only three of the six proposed ACR criteria, the clinical signs of her condition were most distinctive and in keeping with a diagnosis of CSS on clinical grounds. Indeed, Lanham et al have reported that although the classical histological picture comprises a necrotizing vasculitis, eosinophilic tissue infiltration and extravascular granulomas, it is only found in a minority of cases, and is not pathognomonic of the condition.…”
Section: To the Editorsupporting
confidence: 53%
“…1 The presence of four or more criteria yields a sensitivity of 85% and a specificity of 99.7%. These criteria include (1) asthma, (2) eosinophilia of more than 10% in the peripheral blood, (3) paranasal sinusitis, (4) pulmonary infiltrates (may be transient), (5) histological proof of vasculitis with extravascular eosinophils, and (6) mononeuritis multiplex or polyneuropathy. No causes of CSS are known, 2 although possible causes include allergic or autoimmune reactions to an environmental agent or drug (e.g., mesalazine, 3 propylthiouracil 4 ).…”
Section: To the Editormentioning
confidence: 99%
“…The HLA-DRB1 *04 and *07 alleles and the HLADRB4 gene are associated with an increased risk of developing EGPA [7,8]. The finding of an association with HLA, as in other autoimmune diseases, supports the hypothesis of an antigen-targeted disease.…”
Section: Genetic and Environmental Factorsmentioning
confidence: 58%
“…Since anti-neutrophil cytoplasmic antibodies (ANCA) have been found in a proportion of patients, EGPA has subsequently been included in the spectrum of ANCA-associated vasculitis (AAV), along with GPA and microscopic polyangiitis (MPA) [4]. Several studies have elucidated the role of immune mechanisms, identifying genetic associations with HLA-DRB4 while recognizing new diagnostic and follow-up biomarkers (e.g., eotaxin-3) [5][6][7][8][9][10][11]. Finally, the treatment approach has improved through the use of immunosuppressive drugs and biological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, pooling CSS patients with WG and MPA, found a not significant association with a lower frequency of HLA-DRB1*03 (Boki KA, 1997). More recent genetic studies suggested some predisposing hereditary factors, like the HLA-DRB1*04 and HLA-DRB1*07 alleles and the HLA-DRB4 gene, which would be more frequent in Churg-Strauss syndrome patients than in healthy controls (Vaglio A. et al 2007). HLA-DRB4 positive patients were associated with a higher number of vasculitis symptoms, in particular in the ANCA positive group.…”
Section: Geneticsmentioning
confidence: 99%